(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This study reports a bibliographic survey of cooperation studies conducted a) to identify how this phenomenon is characterized and studied in different areas and b) how the study of cooperation can be related to areas of development and evolution and analysis behavior. The selection of the studies was performed in two steps. In the first step, the main Behavior Analysis journals were selected; and, in the second step, a bibliographic search was carried out in five databases with content related to the topic of cooperation. After the exclusion criterion, 41 articles were analyzed from the analysis categories proposed in the study. It can be concluded that the study of cooperation includes the characterization and investigation of different behavioral phenomena, most of them possible to be characterized by the concepts of contingency, control of stimulus and social reinforcement. The main contribution of this study is to encourage concepts of behavior analysis to be integrated into the wide discussion scenario on cooperation, especially those carried out in the areas of development and evolution of human behavior.